2020
DOI: 10.1116/6.0000257
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of SiN etching rate fluctuation in atomic layer etching

Abstract: Note: This paper is part of the Special Topic Collection Commemorating the Career of John Coburn. a)This article is based on material presented at the 66th Symposium of the American Vacuum Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 30 publications
(48 reference statements)
2
28
0
Order By: Relevance
“…It has been reported that the residual CF layer, as F-containing radicals, was released back into the plasma from the reactor walls, which lead to a gradual increase of EPC. ,, Conversely, in the F-deficient condition plasma using CH 3 F/Ar, the buildup of CF x on the chamber walls was observed to cause a decrease of EPC. This is because the C–C bonds in the HFC polymer are difficult to be removed via physical ion bombardment with low energy . Hence, various approaches have been attempted, such as using additional ashing processes or adding O 2 into gas mixtures, to inhibit the formation of residual carbon. ,, Unlike the SiN ALE using CH 3 F/Ar, which presented a decrease in EPC with respect to etch cycle, in this work, the increase in EPC after four cycles is likely due to the reason that the H 2 plasma in the etching step can incorporate with residual carbon, resulting in the formation of HCN by-products with the N in SiN .…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…It has been reported that the residual CF layer, as F-containing radicals, was released back into the plasma from the reactor walls, which lead to a gradual increase of EPC. ,, Conversely, in the F-deficient condition plasma using CH 3 F/Ar, the buildup of CF x on the chamber walls was observed to cause a decrease of EPC. This is because the C–C bonds in the HFC polymer are difficult to be removed via physical ion bombardment with low energy . Hence, various approaches have been attempted, such as using additional ashing processes or adding O 2 into gas mixtures, to inhibit the formation of residual carbon. ,, Unlike the SiN ALE using CH 3 F/Ar, which presented a decrease in EPC with respect to etch cycle, in this work, the increase in EPC after four cycles is likely due to the reason that the H 2 plasma in the etching step can incorporate with residual carbon, resulting in the formation of HCN by-products with the N in SiN .…”
Section: Resultsmentioning
confidence: 89%
“…Consequently, the etch depth deviates from a linear relationship with the cycle number. This phenomenon is a common problem, which has been observed in many systems, particularly in the FC-assisted ALE or cyclic processes. ,,,,, To assess the relationship between the EPC and cycle time (ALE fluctuation), the dependence of EPC on the cycle number of the SiN and SiO 2 films with the HFC deposition step using H 2 /(CF 4 + H 2 ) = 85% plasma for 30s is presented in Figure . The results show that for the SiN ALE, the EPC exhibited a linear relation with the cycle number being increased until 3 with a magnitude of 3.47 nm/cycle.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations